Effects of the lichen Peltigera canina on Cucurbita pepo spp. pepo grown in soil contaminated by DDTs - Akpinar, Aysegul; Cansev, Asuman; İşleyen, Mehmet (Springer Heidelberg, 2021)
Lichens consisting of a symbiotic association of green algae or cyanobacteria and fungi are found in a variety of environmental conditions worldwide. Terricolous lichens, located in soils, affect the living and lifeless environment of the soil due to their effective secondary metabolite and enzymatic content. Terricolous lichens can increase the biological, chemical, and physical usefulness of soil. However, their effects in ensuring the bioavailability of contaminated soil are not known, especially on soil pollution caused by DDTs (p,p '-DDE, p,p '-DDD, p,p '-DDT). This research focuses on the effect of terricolous lichens on zucchini (Cucurbita pepo spp. pepo) grown in soil contaminated by DDTs, utilizing their secondary metabolite and enzymatic contents. Firstly, Peltigera canina, a terricolous lichen species, was added to soil contaminated by DDTs as powdered and intact thallus. After lichen addition to soil, zucchini was planted in. The oxidative stress and antioxidative enzyme activities of zucchini were measured. According to the results, P. canina treatments have a positive effect on the growth and development of zucchini, although oxidative stress was observed. Also, it was determined that powdered application had more effective results than intact thallus application.
Keywords: Lichens; Peltigera canina; DDTs; Soil bioavailability; Oxidative stress; Antioxidative defense system